miR-1269a and miR-1269b: Emerging Carcinogenic Genes of the miR-1269 Family - Xie, Zijun; Zhong, Chenming; Duan, Shiwei (Frontiers in Cell and Developmental Biology, 2022)
miRNAs play an important role in the occurrence and development of human cancer. Among them, hsa-mir-1269a and hsa-mir-1269b are located on human chromosomes 4 and 17, respectively, and their mature miRNAs (miR-1269a and miR-1269b) have the same sequence. miR-1269a is overexpressed in 9 cancers. The high expression of miR-1269a not only has diagnostic significance in hepatocellular carcinoma and non-small cell lung cancer but also is related to the poor prognosis of cancer patients such as esophageal cancer, hepatocellular carcinoma, and glioma. miR-1269a can target 8 downstream genes (CXCL9, SOX6, FOXO1, ATRX, RASSF9, SMAD7, HOXD10, and VASH1). The expression of miR-1269a is regulated by three non-coding RNAs (RP11-1094M14.8, LINC00261, and circASS1). miR-1269a participates in the regulation of the TGF-β signaling pathway, PI3K/AKT signaling pathway, p53 signaling pathway, and caspase-9-mediated apoptotic pathway, thereby affecting the occurrence and development of cancer. There are fewer studies on miR-1269b compared to miR-1269a. miR-1269b is highly expressed in hepatocellular carcinoma, non-small cell lung cancer, oral squamous cell carcinoma, and pharyngeal squamous cell carcinoma, but miR-1269b is low expressed in gastric cancer. miR-1269b can target downstream genes (METTL3, CDC40, SVEP1, and PTEN) and regulate the PI3K/AKT signaling pathway. In addition, sequence mutations on miR-1269a and miR-1269b can affect their regulation of cancer. Future research on miR-1269a and miR-1269b can focus on elucidating more of their upstream and downstream genes and exploring the clinical application value of miR-1269a and miR-1269b.